2016
DOI: 10.1007/s11356-016-6950-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends in atmospheric particulate matter in Dhaka, Bangladesh, and the vicinity

Abstract: Dhaka and its neighboring areas suffer from severe air pollution, especially during dry season (November-April). We investigated temporal and directional variations in particulate matter (PM) concentrations in Dhaka, Gazipur, and Narayanganj from October 2012 to March 2015 to understand different aspects of PM concentrations and possible sources of high pollution in this region. Ninety-six-hour backward trajectories for the whole dry season were also computed to investigate incursion of long-range pollution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 23 publications
3
31
0
Order By: Relevance
“…128 Air pollution is a significant problem specially in the urban areas of Bangladesh with marked temporal and directional variations in particulate matter concentrations. 129 A study to evaluate the emissions and air quality in megacities found Dhaka to have the poorest air quality in respect of total suspended particles (TSP), sulfur dioxide (SO 2 ), and nitrogen dioxide (NO 2 ) among the megacities, and the pollutant levels were far beyond the WHO standard. 130 One recent study involving Dhaka City found elevated concentrations of the number, surface and mass distributions of particulate matters; fine particles (0.5-1.0 µm) derived from vehicle emissions were dominating the aerosol particles number concentrations.…”
Section: Air Pollutionmentioning
confidence: 99%
“…128 Air pollution is a significant problem specially in the urban areas of Bangladesh with marked temporal and directional variations in particulate matter concentrations. 129 A study to evaluate the emissions and air quality in megacities found Dhaka to have the poorest air quality in respect of total suspended particles (TSP), sulfur dioxide (SO 2 ), and nitrogen dioxide (NO 2 ) among the megacities, and the pollutant levels were far beyond the WHO standard. 130 One recent study involving Dhaka City found elevated concentrations of the number, surface and mass distributions of particulate matters; fine particles (0.5-1.0 µm) derived from vehicle emissions were dominating the aerosol particles number concentrations.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Valid data capture of PM 10 and PM 2.5 concentrations in Gazipur during the study period was 94% and 93%, respectively. [4], the meteorology of Dhaka and its vicinity is divided mainly into two groups: (1) dry season (November to April) and (2) wet season (May to October). For air quality study, dry season is further divided into two classes: (a) winter (November to January) and (b) summer (February to April).…”
Section: Observation Site and Data Collection Air Monitoring Station (mentioning
confidence: 99%
“…The city of Dhaka, Bangladesh, and its vicinity severely suffer from high level of particulate matter (PM) concentrations in the atmosphere, especially during dry season (November-April) [1][2][3]. The region experiences several air pollution episodes in winter (November-January) when the atmosphere gets polluted with PM 2.5 concentrations 10-14 times greater than the World Health Organization guideline value [4]. Most of this pollution originates from the local sources like brick manufacturing kilns, vehicles, and resuspended dusts [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollution has become a serious concern for public health in many urban areas of Bangladesh [1,2]. Annual averages of fine particulate matter (PM 2.5 ) concentrations in the air of Dhaka during 2013 to 2014 were found about six times greater than the standards for PM 2.5 in Bangladesh [3]. Higher pollution scenarios usually happen in dry season (November -April), which poses great threat to the human health in the country.…”
Section: Introductionmentioning
confidence: 99%